Reproductive dispersion and damping time scale with life‐history speed - Sha Jiang; Harman Jaggi; Wenyun Zuo; Madan K. Oli; Tim Coulson; Jean‐Michel Gaillard; Shripad Tuljapurkar (Ecology Letters, 2022)
Iteroparous species may reproduce at many different ages, resulting in a reproductive dispersion that affects the damping of population perturbations, and varies among life histories. Since generation time () is known to capture aspects of life‐history variation, such as life‐history speed, does also determine reproductive dispersion () or damping time ()? Using phylogenetically corrected analyses on 633 species of animals and plants, we find, firstly, that reproductive dispersion scales isometrically with . Secondly, and unexpectedly, we find that the damping time () does not scale isometrically with generation time, but instead changes only as with (also, there is a similar scaling with ). This non‐isometric scaling implies a novel demographic contrast: increasing generation times correspond to a proportional increase in reproductive dispersion, but only to a slower increase in the damping time. Thus, damping times are partly decoupled from the slow‐fast continuum, and are determined by factors other than allometric constraints.